2015
DOI: 10.1099/jmm.0.000182
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic surgical prophylaxis increases nasal carriage of antibiotic-resistant staphylococci

Abstract: Staphylococci are a significant cause of hospital-acquired infection. Nasal carriage of Staphylococcus aureus is an important risk factor for infection in surgical patients and coagulase-negative staphylococci (CNS) are a major cause of prosthetic joint infections. The impact that antibiotic surgical prophylaxis has on the nasal carriage of staphylococci has not been studied. Daily nasal swabs were taken from 63 patients who received antibiotic surgical prophylaxis and 16 patients who received no antibiotics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We observed a positive association between previous dispensation of any antibiotics and isolation of MRSA, but caution is needed as MRSA was only isolated in 1.3% of the individuals in our study. This is consistent with previous hospital studies where antibiotic surgical prophylaxis increases nasal carriage of antibiotic-resistant staphylococci [ 23 ]. Evidence seems to indicate that the endogenous microflora of the patient may be critical since clinical studies have found that S. aureus skin colonisation increases the risk of a subsequent infection by three-fold, and up to 80% of cases of staphylococcal bacteraemia are caused by strains identical to those in the patient’s nasal cavity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed a positive association between previous dispensation of any antibiotics and isolation of MRSA, but caution is needed as MRSA was only isolated in 1.3% of the individuals in our study. This is consistent with previous hospital studies where antibiotic surgical prophylaxis increases nasal carriage of antibiotic-resistant staphylococci [ 23 ]. Evidence seems to indicate that the endogenous microflora of the patient may be critical since clinical studies have found that S. aureus skin colonisation increases the risk of a subsequent infection by three-fold, and up to 80% of cases of staphylococcal bacteraemia are caused by strains identical to those in the patient’s nasal cavity [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Staphylococci were cultured on selective media and identified to species level as described previously [8]. In brief, S. aureus and coagulase negative staphylococci (CNS) isolates were preliminary identified by colony morphology from culture media.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic surgical prophylaxis is administered to surgical patients to reduce the risk of postoperative infection. The only culture-dependent study of the impact of antibiotic surgical prophylaxis on the nasal microbiota [8] reported that antibiotics did impact on staphylococcal diversity but that the effect was patient specific. However, a major limitation of the study was the culture-based methodology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increasing occurrence of antibiotic resistance has been recognized to be a global problem. There is also some evidence for selecting antibiotic-resistant staphylococci in relation to wide-range antibiotic prophylaxis [48]. …”
Section: Rationale and Basic Concepts Of Pji Preventionmentioning
confidence: 99%